CDS504 – Enabling Technologies & Infrastructures for Big Data (Teknologi Pengupayaan & Prasarana untuk Data Raya) - February/March 2022 - PPSKOM, Pusat Pengajian Sains Komputer (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 CDS504 – Enabling Technologies & Infrastructures for Big Data (Teknologi Pengupayaan & Prasarana untuk Data Raya) Duration : 2 hours (Masa : 2 jam)